IMPLEMENTASI MEDIA POP-UP DALAM MENGENALKAN KEBERAGAMAN AGAMA UNTUK MENUMBUHKAN SIKAP TOLERANSI ANAK USIA 4-5 TAHUN - Tutut Noviana; Mella Nanda Nurohmah; Erma Fachriani (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
The aim of the research is to describe the implementation of pop-up media as a means of introducing religious diversity to children aged 4-5 years at Pertiwi Kindergarten, Blitar Regency and to reveal the factors that play a role in supporting and hindering the implementation of the media. The approach used is qualitative with descriptive research type. This research involved 14 Group A children as research subjects. Data collection through direct observation, interviews and documentation. The data validity test was carried out by source triangulation. The data analysis process uses interactive Miles, Huberman, and Saldana through the stages of data collection, data condensation, data presentation, and drawing up conclusions. The implementation of pop-up media can support an attractive, active and meaningful learning process, as well as foster interest in learning and an attitude of tolerance. Implementing pop-up media can help children learn about various religions in Indonesia. Supporting factors include interesting media and the teacher's ability to manage learning. Inhibiting factors include children who are still passive at the start of learning, limited media in reaching all children, and media that is easily damaged due to repeated use. So, pop-up media can be an effective alternative learning media in introducing religious diversity to early childhood.